Analisis Tahap Berpikir Geometri Siswa SMA Menurut Tahap Berpikir Van Hiele (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2023)
This type’s of research is a descriptive studies with a qualitative approach that aims to describe the stages of geometric thinking in senior high school students according to Van Hiele's theory. The subjects in this study were students of class X-MIA SMA Plus Darma Siswa consisting of 3 people, namely 1 student with high ability, 1 student with moderate ability and 1 student with low ability. The instrument in this study was the researcher herself as the main instrument guided by valid and reliable geometry ability tests and interview guidelines. The research process follows the stages of: (a) formulating indicators of geometric thinking stages according to Van Hiele's theory based on relevant theory and research, (b) formulating valid and reliable supporting instruments (Van Hiele geometry tests and interview guidelines), (c) conducting collecting data to uncover students' geometric thinking stages on quadrilateral properties, (d) analyzing data on students' thinking stages according to Van Hiele's theory (e) discussing the results of the analysis, (f) making conclusions about the research results. The results showed: (a) KT subjects were at stage 4 (formal deduction) (b) KS subjects were at stage 3 (informal deduction), while (c) KR subjects were at stage 1 (visual).